Process capability improvement through DMAIC for aluminum alloy wheel machining - G. V. S. S. Sharma; P. Srinivasa Rao; B. Surendra Babu (Journal of Industrial Engineering International, 2018)
This paper first enlists the generic problems of alloy wheel machining and subsequently details on the process improvement of the identified critical-to-quality machining characteristic of A356 aluminum alloy wheel machining process. The causal factors are traced using the Ishikawa diagram and prioritization of corrective actions is done through process failure modes and effects analysis. Process monitoring charts are employed for improving the process capability index of the process, at the industrial benchmark of four sigma level, which is equal to the value of 1.33. The procedure adopted for improving the process capability levels is the define-measure-analyze-improve-control (DMAIC) approach. By following the DMAIC approach, the C p, C pk and C pm showed signs of improvement from an initial value of 0.66, -0.24 and 0.27, to a final value of 4.19, 3.24 and 1.41, respectively.
Keywords: 650; Alloy wheel; CTQ (critical-to-quality) characteristic; DMAIC (define-measure-analyze-improve-control); Ishikawa diagram; PFMEA (process failure modes and effects analysis); Control charts